Determination of Rifapentine and 25-O-desacetyl Rifapentine from 100 µl human breastmilk by LC-MS/MS using protein precipitation and solid phase extraction - Mkhize, Buyisile (Department of Medicine, 2020)
There is currently no information available on the transfer of the second-line anti-TB drug, rifapentine and its metabolite, into breastmilk. The subsequent implications to the breastfed infant, as well as consequences of long-term exposure to potentially sub-therapeutic drug levels with regards to the development of drug resistant bacteria is therefore not known. A liquid chromatography method with detection by mass spectrometry (LC-MS/MS) is described for the quantification of rifapentine and its metabolite, 25-O-desacetyl rifapentine in human breastmilk, using rifampicin-d3 as an internal standard. An AB Sciex 4000 mass spectrometer at unit resolution in the multiple reaction monitoring (MRM) mode was used to monitor the transition of the protonated precursor ions m/z 877.5, m/z 835.4 and m/z 827.4 to the product ions m/z 151.1, m/z 453.2 and m/z 151.200 for rifapentine, 25-Odesacetyl rifapentine and rifampicin-d3, respectively. Ions were produced using Electro spray ionisation (ESI) in the positive ionisation mode. An Agilent Poroshell 120 EC-C18 (4.6 x 50 mm, 2.7 μm) column was used for chromatographic separation using an isocratic method of acetonitrile containing 0.1% formic acid and water containing 10% methanol and 0.1% formic acid (55:45, v/v), at a flow rate of 450 µl per minute. The retention times for rifapentine, 25- O-desacetyl rifapentine and rifampicin-d3 were ≈2.67, ≈1.88 and ≈1.96 minutes, respectively. The method was developed and validated according to FDA guidelines. The extraction method consisted of a combination of protein precipitation and C18 solid phase extraction. Rifapentine and 25-O-desacetyl rifapentine showed no significant carry over on the Agilent autosampler. The method was reproducible when analysed with human breastmilk from six different sources from Western Cape Maternity Breastmilk Bank. Rifapentine mean extraction yield was 84.2% (%CV = 1.7) and that of 25-O-desacetyl rifapentine was 71.1% (%CV = 10.8). Rifapentine had a mean process efficiency of 80.4% (%CV = 4.7) and that of 25-O-desacetyl rifapentine was 95.7% (%CV = 5.7). Intra- and inter day validations over 3 days were performed. The calibration curves fit a quadratic regression with 1/x weighting over a concentration range of 2 - 2000 ng/ml for both rifapentine and 25-Odesacetyl rifapentine based on the analyte/internal standard peak area ratios, the accuracy ranged from 92.9% to 105.5% for both rifapentine and 25-O-desacetyl rifapentine standards. The Quality Controls accuracy ranged from 97.4% to 106.0% for both rifapentine and 25-Odesacetyl rifapentine. Stock solutions were shown to be stable for 69 days at -80°C. v Rifapentine and 25-O-desacetyl rifapentine were stable in human breastmilk for up to 72 hours at approximately -80°C and -20°C, on benchtop for ≈4.5 hours on ice and after three freeze-thaw cycles. Rifapentine and 25-O-desacetyl rifapentine were shown to be stable on the autosampler over a period of approximately 48 hours after which the entire batch could be reinjected. Autosampler stability revealed a decrease in peak area ratios, indicating that a partial batch cannot be reinjected after 48 hours in case of instrument failure. This method will be utilized in the analysis of patient samples from a clinical study in South Africa in breastfeeding women with tuberculosis.